Encyclopaedia Britannica deluxe cd 2000. - Encyclopaedia Britannica, inc. (Oxford University Press, 1994)
Electronic encyclopedia containing the entire text of 83000+ articles, 6500+ photos and illustrations, 1 hour video, 1500+ maps, direct access* to 125000+ internet sites through Britannica.co.uk, New Oxford Dictionary of English, Interactive Timeline, New Multimedia spotlichts, new research assistant, new context bar navigation, new quick search